Circular economy : from waste reduction to value creation - Delchet, Karen (Modern finance, management innovation and economic growth set ;, 2020)
This book is aimed at companies, researchers, consultants, consumers, students and any interested public interested in the subject, the reflections and practices of the circular economy. As part of the draft law on the circular economy in France, the authors (researchers and experts) analyze the data and the reflections and base their arguments on real examples in order to propose solutions and recommendations for a green economy. It gives an updated overview of the reflections and practices around the circular economy. The book is divided into three parts: The company and its functions, innovative business models - The institutional, legislative and normative framework - Some sectors of activity with the prism of the circular economy.